“We’re Home Now”: How a Rehousing Intervention Shapes the Mental Well-Being of Inuit Adults in Nunavut, Canada - Karine Perreault; Josée Lapalme; Louise Potvin; Mylène Riva (International Journal of Environmental Research and Public Health, 2022)
This study explores the ways in which a rehousing intervention shapes the mental well-being of Inuit adults living in Nunavut, Canada, where the prevalence of core housing need is four times the national average. More specifically, it compares the housing experiences of participants who were rehoused in a newly built public housing unit, to the experiences of participants on the public housing waitlist. The study was developed in collaboration with organizations based in Nunavut and Nunavik. Semi-structured interviews were transcribed, and a deductive-inductive thematic analysis was performed based on Gidden’s concept of ontological security, and Inuit-specific mental health conceptualization. Twenty-five Inuit adults participated (11 rehoused, 14 waitlist). Three themes were identified to describe how the subjective housing experiences of participants improved their mental well-being after rehousing: (1) refuge creation; (2) self-determination and increased control; (3) improved family dynamics and identity repair. Implicit to these themes are the contrasting housing experiences of participants on the waitlist. Construction initiatives that increase public housing stock and address gaps in the housing continuum across Inuit regions could promote well-being at a population level. However, larger socio-economic problems facing Inuit may hamper beneficial processes stemming from such interventions.